Análise dos aspectos envolvidos na condução de contratos de terceirização de tecnologia da informação - Cruz, Marcelo Alves (2014)
Outsourcing Information Technology services is a growing practice among organizations of many sizes and sectors, where the relationship between contractor and supplier is usually governed by contracts. Contracts are devices intended to govern rights and obligations between the parties. Due to the impossibility of the parties foresee all future contingencies and also due to the imprecision of the written language, contracts are usually recognized in economics as fundamentally incomplete. This raises the possibility of classifying contracts as predominantly formal, those written in completeness of structure that is sufficient to guide the relationship between the parties, and predominantly relational, those whose formal structure is insufficient to coordinate the relationship, and so require additional communication and interaction mechanisms for the relationship between the parties to properly occur around the contractual object. The structure of incentives is among the mechanisms used in formal contracts to signal desired behaviors to the parties. Little has been studied about the effect of the combination between incentive structures and relational mechanisms on the progress of contracts. This study examines the effects of formal mechanisms of incentive structures and relational mechanisms on the progress of the contract, using hiring outsourcing of Information Technology (IT) services as context. The results of the three main chapters of this study, set as formal academic papers, derive high explanatory power of interactions between incentive structures, relational governance, supplier behavior and expectation of success. Similarly, antecedents and combined effects are analyzed and discussed. From the standpoint of the contribution to managerial practice, the work as a whole contributes to improve hiring decisions of IT services, formulating more effective contracts, and offers assistance in choosing the most appropriate contracting mechanisms to the context of the contractor.